Festa dos Bárbaros - Klein, Paula Maria Garulo y (2022)
This work aims to propose a report on the activities of a theater artist from São Paulo City during the pre and post-pandemic of COVID-19. It also tells a little about the work of the Cia. Trupe Liuds, a circus group that proposes research on black comedy, headquartered in the Quilombaque Cultural Community in Perus, on the outskirts of São Paulo. It discusses the show "Festa dos Bárbaros", by Cia. São Jorge de Variedades, from its conception to its in-person premiere. And, above all, it talks about the curious junction of Jurema Sagrada with the Guerra dos Bárbaros, also known as the Confederação dos Cariris. That explains the researcher's difficulty in pursuing her doctorate in the face of the spread of the disease and the growing political violence that the Brazilian government inflicted against the people from 2019 to 2022. Completing this work required a collective effort, without which it would be impossible to finish